APLIKASI PORTAL PERLINDUNGAN KONSUMEN (APPK) OTORITAS JASA KEUANGAN PENAJAMAN ASPEK PERLINDUNGAN PADA SISTEM JASA KEUANGAN - Bernadetta Tjandra Wulandari (Jurnal Hukum dan Bisnis (Selisik), 2022)
The financial industry has a major role in supporting development and the country’s economy as well as placing the consumer community using financial services as the party who holds an important position in it. Aspects of trust and efforts to protect consumers of financial services are points that need attention and are constantly being pursued in order to increase trust in Financial Services Businesses and their products (market confidence), thus indirectly maintaining the sustainability of the financial industry itself. The financial services industry, which generally utilizes high technology, has a large potential for harm to consumer users which then leads to legal disputes. Efforts to resolve the dispute will have a different dimension if it is carried out through legal channels which are generally taken, namely through the courts, compared to settlement through out-of-court settlement mechanisms. The nature of the judiciary with all its characteristics is seen as not meeting the efficiency aspect for consumer disputes. Therefore, a quick, low-cost and short settlement is considered more appropriate for consumer dispute cases. Complaint handling and dispute resolution mechanisms that are effective and efficient on the one hand will strengthen consumer protection and on the other hand, in addition to supporting the development of the financial services sector, will also increase and improve the welfare of consumers and society